Achievement Management Model of Secondary Schools in the Northeastern Region - Phola, Sombut; Kosonkittiumporn, Saowalak; Kaenapoom, Sanya (Journal of Graduate MCU KhonKaen Campus, 2019)
This research The objective is to: 1) synthesize the theoretical framework for achievement management of secondary schools in the central northeastern region 2) study factors affecting achievement-oriented management of secondary schools Central Northeastern Region 3) Create a model of achievement-oriented management of secondary schools in the area And 4) confirm the model of achievement-oriented management of secondary schools in the central northeastern region that the researcher created By studying the factors that affect the effectiveness of the management-oriented model, the achievement is the human factor, the mechanism and the environment How to conduct research Mixed Method Research by applying quantitative and qualitative research To apply and blend together, there are 3 phases: Phase 1 is the concept of the theory Define conceptual framework And bring questionnaires to quantitative research To study the factors affecting the effectiveness of the achievement-oriented management, Phase 2 is qualitative research To create a pattern and Phase 3 is a qualitative research To confirm the management style of achievement with the expert group Educational experts The research found that From the conception of the administration theory Set the conceptual framework into 3 factorsNamely 1) personal factors, 2) mechanical system factors, and 3) environmental factors Factors affecting achievement-oriented management of secondary schools in the central northeastern region Overall, the practice was at a high level (3.97) and when considered individually, the order factors were the mechanical system factors. There is a high level of practice (4.06). Environmental factors There is a high level of practice (4.05) and personal factors. There was a high level of practice ( 3.80), respectively. Of achievement-oriented management of secondary schools in the central northeastern region, with 4 main components as follows: 1) environmental factors 2) personal factors and 3) Mechanism factors Confirmation of the effectiveness model of achievement-oriented management of secondary schools in the central northeast area By experts Educational experts Found that the appropriateness of the effectiveness model of achievement-oriented management of secondary schools in the central northeast area The overall level is at the highest level ( 4.81). When considering each element, it is found that it is at the highest level in all components. Is suitable at the highest level in all components It was found that the elements with the highest mean value were personal elements (4.90), followed by mechanical components (4.75). The lowest mean components were environmental elements (4.70) From the above results, it can be seen that environmental factors have the highest path coefficient. Followed by personal factors and mechanical system factors affecting the achievement-oriented management of secondary schools in the central northeastern region Therefore, the Office of Education and Schools Under the Office of Secondary Education Area Central Northeast Should encourage school administrators Or related persons have taken action and given importance to environmental factors such as the use of technology media Physical environment And corporate culture Personal factors in managing talent Learning management And studying student backgrounds to be used as a database for improvement Developed individually Therefore, the effectiveness model of achievement-oriented management of secondary schools in the central northeast region Developed this time Is appropriate at the highest level Through the Office of Educational Service Area And other educational institutions, therefore, can be applied in the development of quality achievement of educational institutions as appropriate and necessary requirements